Diskusi Psikologi Positif dan Al-Quran Tentang Jantung (Qalb atau Heart) - Ahmad Muhammad Diponegoro (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
According to recent research, the heart is not only pumping blood but is a very complex organ. Recent studies indicated that the heart is able to think, feel, communicate. Furthermore, the heart is the organ that exceeds the ability of the brain intuitive. According to the Encyclopedia of Positive Psychology (Lopez,2009)   , the heart is able to gives the command more to the brain than the brain to the heart. Chapters in both Al-Quran and Tafseer briefly discusses the Qalb. Results of recent study confirmed the words of God in the Qur'an that the Qalb or heart is able to think, consider, regard, and decide.Key words: heart, brain, positive psychology